2017
DOI: 10.3390/molecules22101649
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Total Triterpenoid Saponins Isolated from the Seeds of the Tea Plant (Camellia sinensis) on Human Ovarian Cancer Cells

Abstract: Ovarian cancer is regarded as one of the most severe malignancies for women in the world. Death rates have remained steady over the past five decades, due to the undeniable inefficiency of the current treatment in preventing its recurrence and death. The development of new effective alternative agents for ovarian cancer treatment is becoming increasingly critical. Tea saponins (TS) are triterpenoidsaponins composed of sapogenins, glycosides, and organic acids, which possess a variety of pharmacological activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…The saponins have been found to have numerous pharmacological effects including anti-fungal [ 29 ], anti-viral [ 30 ], anti-inflammatory [ 31 ], anti-hyperlipidemic [ 32 ], immunomodulatory [ 33 ] and anti-tumor activities [ 17 , 19 ]. Among these, TSE 1 was proved to have higher bioactivity than other saponin monomers present in tea seeds [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The saponins have been found to have numerous pharmacological effects including anti-fungal [ 29 ], anti-viral [ 30 ], anti-inflammatory [ 31 ], anti-hyperlipidemic [ 32 ], immunomodulatory [ 33 ] and anti-tumor activities [ 17 , 19 ]. Among these, TSE 1 was proved to have higher bioactivity than other saponin monomers present in tea seeds [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the IC 50 value of TSE 1 for normal ovarian surface epithelial cell line IOSE-364 was 23.82 µM, TSE 1 showed a much lower cytotoxic effect against normal ovarian epithelial cells. In addition, our published data showed that the IC 50 values of cisplatin, which is the most effective and widely used chemotherapeutic agent, were 11.91 µg/mL (35.71 µM) for A2780/CP70 and 10.10 µg/mL (30.30 µM) for OVCAR-3, respectively [ 19 ]. All data taken together, we indicated that TSE 1 exhibited higher inhibitory effects compared to cisplatin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the protective effects of C. sinensis were demonstrated in different types of cancers such as breast, ovarian, prostate and pancreatic cancers. The importance of anti-cancer activity of tea was highlighted (6)(7)(8)(9) In the current study, the effects of the extract from C. sinensis on cytotoxicity, proliferation, apoptosis and oxidative stress status were investigated in rat insulinoma INS-1 cells.…”
Section: Introductionmentioning
confidence: 98%